Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Pada Cafe Bree Sweetandfreeze Banjarmasin (Menggunakan Analisis SWOT) - Nina Rezeki Amalia; Farida Yulianti; Abdul Kadir (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This study aims (1) to determine the marketing strategy used by Cafe Bree Sweetandfreeze Banjarmasin in increasing sales. (2) To find out marketing strategies that can be implemented by utilizing SWOT analysis to improve marketing performance at Cafe Bree Sweetandfreezee in Banjarmasin. The method in this study uses a qualitative descriptive method. The informants in the study were the Owners of Cafe Bree Sweetandfreeze Banjarmasin. Data collection techniques used in this study are observation techniques, interviews and documentation studies. The results of the study show that Cafe Bree Sweetandfreeze Banjarmasin uses various marketing strategies, such as advertising promotions, collaboration with influencers, new product development and creating Instagramable photo areas. The SWOT analysis shows strengths in product quality, cafe design and strategic location, while weaknesses relate to understanding customer preferences and digital marketing. The cafe has opportunities in forging local partnerships and leveraging social media, but faces threats from intense competition and changing consumer trends. In conclusion, Cafe Bree Sweetandfreezee Banjarmasin can capitalize on strengths, overcome weaknesses and seize opportunities to strengthen their brand and increase their market share.